An Initial Investigation of the Effects of Mulch Layers on Soil-Dwelling Arthropod Assemblages in Vineyards - Addison, P.; Baauw, A.H.; Groenewald, G.A. (South African Journal of Enology and Viticulture, 2013)
The use of mulches is gaining worldwide attention in a number of different crops, including vineyards. However, the effects of mulches on arthropod assemblages are not well documented. We therefore conducted an initial investigation into the effects of three different types of mulch on arthropod assemblages in vineyards. Sampling took place from March to June 2010 on four wine grape farms in the Stellenbosch/ Paarl region using pitfall traps. All arthropods were identified to family level and classified into functional feeding groups. A total of forty different families of springtail (Collembola) and insect (Insecta) were recorded. Cluster analysis indicated a high degree of similarity between the mulch sites and also between the control sites, based on soil-dwelling arthropod diversity. Springtails and ants were most abundant and could be used as reference organisms for future, larger-scale studies on mulches.